Hybrid study of digital entrepreneurship in the COVID-19 era - RincÃ³n Ornelas, Rosa MarÃa; Zallas Esquer, Lidia Amalia; Sanchez Sanchez, Arturo; GarcÃa Lirios, Cruz; Chaparro Medina, Jorge E.; RincÃ²n RodrÃ¬guez, Isabel Cristina (Journal of Sustainable Economics, 2023)
The objective of this work was to specify a model for the study of electronic consumption. An exploratory, cross-sectional and psychometric study was conducted with a selection of Internet users, considering their time of use. An associative perceptual structure was found between the usefulness of the technology and the effectiveness of the respondent, although the research design limited the results to the research sample, suggesting the extension of the work towards other cybernetic contexts.